Correlates of e-cigarette use among adults initiating smoking cessation treatment. (1st July 2021) - Boozary, Laili Kharazi; Frank-Pearce, Summer G.; Alexander, Adam C.; Waring, Joseph J.C.; Ehlke, Sarah J.; Businelle, Michael S.; Cohn, Amy M.; Kendzor, Darla E.
Highlights: Baseline dual CC/EC users were more CC dependent than CC-only users. EC use prior to a CC quit attempt was not associated with CC cessation. More frequent baseline EC use predicted a lower likelihood of CC cessation. Abstract: Background: Little is known about the correlates of e-cigarette (EC) use among adults seeking smoking cessation treatment, and it is unclear how EC use affects smoking treatment outcomes. Methods: Participants were 649 adult smokers enrolled in smoking cessation treatment. Participants completed a baseline (pre-quit) assessment with follow-up at 4-, 12-, and 26-weeks after a scheduled combustible cigarette (CC) cessation date. EC use was described before and after the CC cessation date, and the impact of baseline EC use on CC cessation at follow-up was evaluated. Results: At baseline, 66.6 % of participants had ever-used ECs and 23.1 % reported past 30-day EC use. Past 30-day EC users were younger, more socioeconomically disadvantaged, more CC dependent, and less likely to report Black race compared to non-users. At the 4-, 12-, and 26-week follow-ups, 6.4 %, 7.4 %, and 8.1 % reported dual EC/CC use; and 2.7 %, 3.4 %, and 2.7 % had switched to exclusive EC use. Past 30-day EC use at baseline was not associated with CC cessation at any follow-up. However, among baseline past 30-day EC users ( n = 150), using ECs ≥ once per week was associated with a lower likelihood of CC cessation at 26-week follow-up (adjusted OR 0.346, 95 % CI: 0.120, 0.997). Conclusion: Findings indicated that dual users of CCs and ECs at baseline differed from CC-only users on sociodemographic and smoking characteristics. Baseline EC use did not impact smoking cessation overall. However, among past 30-day users, more frequent EC use at baseline adversely impacted longer-term cessation outcomes, perhaps due to greater baseline CC/nicotine dependence.